The Effect of the Learning Model Contextual Teaching and Learning (CTL) and Interest on the Students' Natural Sciences Learning Outcomes in Class VI Toboali District Elementary School - Farrina Veranicha; Maman Rumanta; Ucu Rahayu (Budapest International Research and Critics University, 2021)
This research aims to describe the effect of the Contextual Teaching and Learning learning model on students' interest and learning outcomes in class VI SD Negeri in Toboali District, Bangka Selatan Regency, the academic year 2019/2020. This type of research is a 2x2 factorial quasi-experiment. The population of this study were students of class VI SD Negeri in Toboali District. The sample in this study were students of class VI SD Negeri 18 Toboali, totalling 38 students with 19 students in the experimental class I and 19 students in the experimental class II. Student interest in learning was collected using a questionnaire, while data on student learning outcomes were obtained through posttests. The data obtained were analyzed using Two Way Anova with a significance level of 0.05, assisted by SPPS 24.00 for windows. The results showed differences in science learning outcomes in students who had high interest in learning with students who had low learning interests. There were no differences in learning outcomes in classes taught using Contextual Teaching and Learning assisted by video learning or classes taught using Contextual Teaching and learning assisted with teaching aids. There is no interaction between interest in learning and science learning outcomes of grade VI public SD students in Toboali District.